2021
DOI: 10.3390/biomedicines9050519
|View full text |Cite
|
Sign up to set email alerts
|

NOD1-Targeted Immunonutrition Approaches: On the Way from Disease to Health

Abstract: Immunonutrition appears as a field with great potential in modern medicine. Since the immune system can trigger serious pathophysiological disorders, it is essential to study and implement a type of nutrition aimed at improving immune system functioning and reinforcing it individually for each patient. In this sense, the nucleotide-binding oligomerization domain-1 (NOD1), one of the members of the pattern recognition receptors (PRRs) family of innate immunity, has been related to numerous pathologies, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 129 publications
(188 reference statements)
0
11
0
Order By: Relevance
“…NOD1, a member of the pattern recognition receptor (PRR) family, is involved in various pathologies, especially cancer. NOD1 is expressed in some types of cells, including endothelial cells, hematopoietic cells and various immune cells (e.g., neutrophils, macrophages, monocytes, NK cells, and lymphocytes) [ 48 ]. These findings are consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…NOD1, a member of the pattern recognition receptor (PRR) family, is involved in various pathologies, especially cancer. NOD1 is expressed in some types of cells, including endothelial cells, hematopoietic cells and various immune cells (e.g., neutrophils, macrophages, monocytes, NK cells, and lymphocytes) [ 48 ]. These findings are consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide-binding oligomerization domain 1 (NOD1) has been reported to be involved in innate immunity, acting as a pattern-recognition receptor (PRR) that binds to bacterial peptidoglycans and initiates inflammation [ 30 , 31 ]. In 2006, da Silva Correia et al reported that NOD1 inhibited estrogen-dependent breast tumor growth [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…NOD1 has an important role not only in defending hosts against pathogens but also in maintaining tissue homeostasis by regulating cell apoptosis, and the inflammatory and tissue repair responses to injury. Recent studies have shown that NOD1 has an important role in controlling tumorigenesis 6 , 7 . Several crucial proteins, NOD1, RIPK2 (receptor-interacting serine-threonine kinase 2), caspase-12 and human β Defensin 1, 2, 3 (hBD1, 2, 3) participate in or regulate the NOD1 signaling pathway 8 .…”
Section: Introductionmentioning
confidence: 99%